Quercetin, rutin, proanthocyanidin, catechin and epitacethin as fatty acid synthase inhibitor using virtual screening - Candra Rini Hasanah Putri; Sutiman Bambang Sumitro; Setyawati Karyono (The East Java Biological Society, 2017)
Fatty acid synthase is known to participate in the occurrence of malignancies, so fatty acid synthase inhibition is expected can restrain malignancy. In this research, virtual screening is done by molecular docking between the active ingredients in Tamarindus indica with three domains of FAS. In thioesterase domain, it turns out all of the active ingredients in Tamarindus indica can bind thioesterase domain right in the place where orlistat (as a reference inhibitor) bonded, with a higher strength than the orlistat. In enoyl [acyl-carrier-protein] reductase domain, it turns out the binding affinity of quercetin, rutin, catechin and epicatechin against fatty acid synthase are greater than the reference inhibitor, triclosan. In malonyl-CoA / acetyl-CoA-ACP-transacylase domain, it turns out the binding affinity of quercetin, rutine, proanthocyanidin, and catechin against fatty acid synthase is greater than the natural substrate, Malonyl-CoA. The high binding affinity of the active ingredients in Tamarindus indica against the two domains of fatty acid synthase that may also can be occupied by reference inhibitors, showed the ability of Tamarindus indica as an inhibitor of fatty acid synthase. While the high ability of active ingredients in Tamarindus indica to bind to a domain that should be occupied by the natural substrate of fatty acid synthase (malonyl-CoA) demonstrated the ability of Tamarindus indica to inhibit fatty acid synthase's work in a way to compete with the natural substrate. This study shows that Tamarindus indica may serve as anti-malignancy through its ability to inhibit fatty acid synthase.